Psychometric Properties of a Short Measure for South African First-Year Students’ Perceptions of Fit with their Courses of Study (Journal of Student Affairs in Africa, 2022)
The first year of higher education is one of the most critical and challenging times in a student’s lifeand choosing a specific course of study can be very difficult. Often, first-year students realize theyhave different expectations from the courses of study they chose and perceive that their abilities,skills, interests, and ambitions for a future career do not match their chosen courses of study. Whenthe wrong choice has been made, and there is no intervention to choose a course with a moreappropriate fit, students may decide to leave university prematurely, which may have a major impacton a student’s life. Identifying students who do not experience alignment with their choice of studycourse, and offering these students assistance and guidance, is imperative for universities to retainas many students as possible. Unfortunately, there is a paucity of research on a short scale thatmeasures student-course fit validly and reliably, and which can be fairly applied to different groupsin an unbiased manner. This study analyses the psychometric properties of a measure of students’perceptions of fit with their course of study, adapted from a widely used person-job fit scale. Statisticaltechniques used to determine the validity and reliability of this scale were structural validity,differential item functioning to determine item bias, measurement invariance, and reliability.A quantitative, cross-sectional design was used. A sample (N = 1,211) of South African first-yearuniversity students studying at a university with three different campuses was used. As expected,confirmatory factor analysis provided evidence of a one-factor structure. No item bias was presentfor language and gender groups. Although item bias was present for item 2 between campuses,the post hoc analysis indicated that the impact was practically negligible. Measurement invariancewas established, as well as good reliability of the scale. The findings of this study can contribute toknowledge concerning the valid, reliable and fair measurement of first-year students’ perceived fitwith their courses of study. In addition, insights could assist universities in identifying students whoneed proper career guidance to better match with their chosen courses of study.